USING METAPHOR IN EFL CLASSROOM TO ENHANCE WRITING SKILLS: A CASE STUDY - Thu, Nguyen Thi Hong (International Journal of Humanity Studies (IJHS), 2019)
This study is aimed to investigate the effects of using metaphor in the development of writing skill as well as find out the challenges learners may face, then propose the suitable suggestions to boost metaphoric awareness and competence in learning English. The writer conducted two measuring instruments: pro- and pre-test for two groups (control and experimental) to examine the effectiveness of using metaphor in writing; two questionnaires to measure the attitude of the students towards using metaphor in writing that was conducted basing on a 5 point Likert-scale. The study’s participants were 40 English major students at Hanoi Law University. The findings from the study showed that learners with the instruction from teachers on metaphor in songs when writing tended to get better scores than the other ones. However, they also showed that although it is important to learn metaphor, a lot of challenges still maintain. The paper hopefully helps learners have new insight into aspects of figurative language studies and pedagogical applications.DOI: 10.24071/ijhs.2019.030101